Osteogenic Potential of Dental Mesenchymal Stem Cells in Preclinical Studies: A Systematic Review Using Modified ARRIVE and CONSORT Guidelines - Murali Ramamoorthi; Mohammed Bakkar; Jack Jordan; Simon D. Tran (Stem Cells International)
Background and Objective. Dental stem cell-based tissue engineered constructs are emerging as a promising alternative to autologous bone transfer for treating bone defects. The purpose of this review is to systematically assess the preclinical in vivo and in vitro studies which have evaluated the efficacy of dental stem cells on bone regeneration. Methods. A literature search was conducted in Ovid Medline, Embase, PubMed, and Web of Science up to October 2014. Implantation of dental stem cells in animal models for evaluating bone regeneration and/or in vitro studies demonstrating osteogenic potential of dental stem cells were included. The preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines were used to ensure the quality of the search. Modified ARRIVE (Animal research: reporting in invivo experiments) and CONSORT (Consolidated reporting of trials) were used to critically analyze the selected studies. Results. From 1914 citations, 207 full-text articles were screened and 137 studies were included in this review. Because of the heterogeneity observed in the studies selected, meta-analysis was not possible. Conclusion. Both in vivo and in vitro studies indicate the potential use of dental stem cells in bone regeneration. However well-designed randomized animal trials are needed before moving into clinical trials.